Human Resources Investment through the Scholarship Program Implementation for Sustainable Development in the Local Region - Handoko Wijoyo; Faridatul Istighfaroh; Saiful Anam (Jurnal Ekonomi Pembangunan, 2022)
Bojonegoro is the region that contributes 30 percent of national oil, so it is hoped that natural resources can be converted into human resources which are sustainable development investments, looking at the future of Bojonegoro Regency from the HDI perspective to achieve the largest target, whether the policy about scholarships taken has full implications for sustainable development, the researcher is using the Double Exponential Smoothing method. Data were obtained from the Regional Development Planning Agency and the Statistics of Bojonegoro report. Based on the calculation results, the best forecasting is obtained based on the measurement accuracy value of 0.7 MAPE  0.385 persen means that its very good criteria, with many scholarship programs from 2019-2021, concludin using qualitative methods plus 2022 Village RPL scholarships with the number of thousands of people, after graduating in 2024 IPM Bojonegoro is predicted to enter the high category, namely the highest score of 72.08 even more, as an outcome of the program it can be practiced because it is intended for stakeholders and structural drivers of villages in Bojonegoro, and this is in line with sustainable development.